Influence of alcoholism and cholesterol on TSPO binding in brain: PET [11C]PBR28 studies in humans and rodents - Sung Won Kim; Corinde E. Wiers; Ryan E. Tyler; Ehsan Shokri‐Kojori; Yeon Joo Jang; Amna Zehra; Clara Freeman; Veronica Ramirez; Elsa Lindgren; Gregg Miller; Elizabeth Cabrera; Tyler Stodden; et al. (2018)
Neuroinflammation appears to contribute to neurotoxicity observed with heavy alcohol consumption. To assess whether chronic alcohol results in neuroinflammation we used PET and [11C]PBR28, a ligand that binds to the 18-kDa translocator protein (TSPO), to compare participants with an alcohol use disorder (AUD: n = 19) with healthy controls (HC: n = 17), and alcohol-dependent (n = 9) with -nondependent rats (n = 10). Because TSPO is implicated in cholesterol's transport for steroidogenesis, we investigated whether plasma cholesterol levels influenced [11C]PBR28 binding. [11C]PBR28 binding did not differ between AUD and HC. However, when separating by TSPO genotype rs6971, we showed that medium-affinity binders AUD participants showed lower [11C]PBR28 binding than HC in regions of interest (whole brain, gray and white matter, hippocampus, and thalamus), but no group differences were observed in high-affinity binders. Cholesterol levels inversely correlated with brain [11C]PBR28 binding in combined groups, due to a correlation in AUD participants. In rodents, we observed no differences in brain [11C]PBR28 uptake between alcohol-dependent and -nondependent rats. These findings, which are consistent with two previous [11C]PBR28 PET studies, may indicate lower activation of microglia in AUD, whereas failure to observe alcohol effects in the rodent model indicate that species differences do not explain the discrepancy with prior rodent autoradiographic studies reporting increases in TSPO binding with chronic alcohol. However, reduced binding in AUD participants could also reflect competition from endogenous TSPO ligands such as cholesterol; and since the rs6971 polymorphism affects the cholesterol-binding domain of TSPO this could explain why differences were observed only in medium-affinity binders.